Auditory rehabilitation after stroke: treatment of auditory processing disorders in stroke patients with personal frequency-modulated (FM) systems. Issue 6 (13th March 2017) - Koohi, Nehzat; Vickers, Deborah; Chandrashekar, Hoskote; Tsang, Benjamin; Werring, David; Bamiou, Doris-Eva
Abstract: Purpose: Auditory disability due to impaired auditory processing (AP) despite normal pure-tone thresholds is common after stroke, and it leads to isolation, reduced quality of life and physical decline. There are currently no proven remedial interventions for AP deficits in stroke patients. This is the first study to investigate the benefits of personal frequency-modulated (FM) systems in stroke patients with disordered AP.Methods: Fifty stroke patients had baseline audiological assessments, AP tests and completed the (modified) Amsterdam Inventory for Auditory Disability and Hearing Handicap Inventory for Elderly questionnaires. Nine out of these 50 patients were diagnosed with disordered AP based on severe deficits in understanding speech in background noise but with normal pure-tone thresholds. These nine patients underwent spatial speech-in-noise testing in a sound-attenuating chamber (the "crescent of sound") with and without FM systems.Results: The signal-to-noise ratio (SNR) for 50% correct speech recognition performance was measured with speech presented from 0° azimuth and competing babble from ±90° azimuth. Spatial release from masking (SRM) was defined as the difference between SNRs measured with co-located speech and babble and SNRs measured with spatially separated speech and babble. The SRM significantly improved when babble was spatially separated from target speech, while the patients had the FM systems in their ears compared to without the FM systems.Conclusions: Personal FM systems may substantially improve speech-in-noise deficits in stroke patients who are not eligible for conventional hearing aids. FMs are feasible in stroke patients and show promise to address impaired AP after stroke. Implications for Rehabilitation: This is the first study to investigate the benefits of personal frequency-modulated (FM) systems in stroke patients with disordered AP. All cases significantly improved speech perception in noise with the FM systems, when noise was spatially separated from the speech signal by 90° compared with unaided listening. Personal FM systems are feasible in stroke patients, and may be of benefit in just under 20% of this population, who are not eligible for conventional hearing aids.